DAMPAK PEMAHAMAN PSIKOLOGI PENDIDIKAN GURU TERHADAP KEDISIPLINAN SISWA DI SEKOLAH DASAR - Amri Suganda Sianturi (STKIP Subang, 2026)
This study aims to analyze the impact of teachers' understanding of educational psychology on student discipline in elementary schools. Discipline is an important aspect in character building and student learning success, yet various disciplinary behavior problems are still found in the school environment. This study used a literature study method by reviewing journals, books, and scientific articles relevant to educational psychology and student discipline. Data were systematically analyzed to determine the relationship between teacher competence in educational psychology and student disciplinary behavior. The results of the study indicate that teachers' understanding of educational psychology has a significant influence on improving student discipline. Teachers who understand the characteristics of student development are able to manage classes effectively, build positive interpersonal relationships, implement preventive discipline, and create a conducive learning environment. In addition, empathetic communication, positive reinforcement, and collaboration with parents strengthen the implementation of discipline in schools. Conversely, a lack of understanding of educational psychology can lead to weak classroom management and an increase in undisciplined behavior. Therefore, strengthening teacher competence in the field of educational psychology is necessary to build student discipline and support the achievement of educational goals in elementary schools. Keywords: Educational Psychology, Student Discipline, Elementary School